Subcortical surface morphometry in substance dependence: An ENIGMA addiction working group study. (20th November 2019) - Chye, Yann; Mackey, Scott; Gutman, Boris A.; Ching, Christopher R.K.; Batalla, Albert; Blaine, Sara; Brooks, Samantha; Caparelli, Elisabeth C.; Cousijn, Janna; Dagher, Alain; Foxe, John J.; Goudriaan, Anna E.; et al.
Abstract: While imaging studies have demonstrated volumetric differences in subcortical structures associated with dependence on various abused substances, findings to date have not been wholly consistent. Moreover, most studies have not compared brain morphology across those dependent on different substances of abuse to identify substance‐specific and substance‐general dependence effects. By pooling large multinational datasets from 33 imaging sites, this study examined subcortical surface morphology in 1628 nondependent controls and 2277 individuals with dependence on alcohol, nicotine, cocaine, methamphetamine, and/or cannabis. Subcortical structures were defined by FreeSurfer segmentation and converted to a mesh surface to extract two vertex‐level metrics—the radial distance (RD) of the structure surface from a medial curve and the log of the Jacobian determinant (JD)—that, respectively, describe local thickness and surface area dilation/contraction. Mega‐analyses were performed on measures of RD and JD to test for the main effect of substance dependence, controlling for age, sex, intracranial volume, and imaging site. Widespread differences between dependent users and nondependent controls were found across subcortical structures, driven primarily by users dependent on alcohol. Alcohol dependence was associated with localized lower RD and JD across most structures, with the strongest effects in the hippocampus, thalamus, putamen, and amygdala. Meanwhile, nicotine use was associated with greater RD and JD relative to nonsmokers in multiple regions, with the strongest effects in the bilateral hippocampus and right nucleus accumbens. By demonstrating subcortical morphological differences unique to alcohol and nicotine use, rather than dependence across all substances, results suggest substance‐specific relationships with subcortical brain structures. Abstract : This study conducted by the addiction working group of the Enhancing NeuroImaging Genetics through Meta‐Analysis (ENIGMA) Consortium leverages multinational datasets to examine subcortical surface morphology in 1628 nondependent controls and 2277 individuals with dependence on alcohol, nicotine, cocaine, methamphetamine, and/or cannabis. Widespread differences between dependent users and nondependent controls were found, driven primarily by users dependent on alcohol. Alcohol dependence was associated with localized deflation across most structures, with strongest effects in the hippocampus, thalamus, putamen, and amygdala.